Spindle cell lipoma of the tongue: A case report of unusual occurrence - Júnior, Orlando Cavezzi; De Aguiar, Eduardo Castro Guerra; Sartori, José Henrique França; Lima, Flávio de Oliveira [UNESP] (Wolters Kluwer, 2013)
Spindle cell lipoma (SCL) is a benign lipomatous tumor predominantly occurring at the posterior neck and shoulder area. Face, forehead, scalp, cheek, perioral area, and upper arm are less common sites. In oral cavity, it is a relatively uncommon neoplasm, particularly in tongue, which is relatively devoid of fat cells. We present a case report of SCL located on the left lateral border of the tongue in a 64-year-old Caucasian female patient with diabetes mellitus type 2 and arterial hypertension.
Keywords: Oral cavity; spindle cell lipoma; tongue